Možni vzroki obremenjenosti zdravnikov družinske medicine v Sloveniji - Živčec Kalan, Gordana (Zdravstveno varstvo, 2003)
Health care systems in most West European countries, including Slovenia, place great emphasis on primary health care. Family practitioners are confronted with an ever-growing demand in terms of quality and quantity of health services they provide. In addition, primary health care is facing multiple epidemiological and demographical changes (e.g.a growing number of patients with multiple chronic conditions), ageing of the population and an ever-greater complexity of medicine. Numerous rationalization processes in thedelivery of health care, such as shortening of hospital stay, have increased pressure on family practitioners. All these challenges and changes add to stress and lead to poorer performance of family practitioners. Further research will be needed to determine the amount of work-load that family practitioners are still able to cope with, and to find ways to best equip themfor the provision of modern primary health care.
Keywords: družinska medicina; obremenjenost; Slovenia; Slovenija; stres; zdravniki